2008
DOI: 10.1172/jci33328
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging in mice reveals local cell dynamics and inflammation in obese adipose tissue

Abstract: To assess physiological and pathophysiological events that involve dynamic interplay between multiple cell types, real-time, in vivo analysis is necessary. We developed a technique based on confocal laser microscopy that enabled us to analyze and compare the 3-dimensional structures, cellular dynamics, and vascular function within mouse lean and obese adipose tissue in vivo with high spatiotemporal resolution. We found increased leukocyte-EC-platelet interaction in the microcirculation of obese visceral adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
186
1
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(205 citation statements)
references
References 51 publications
9
186
1
9
Order By: Relevance
“…There was also a signi cantly positive relationship between VisF / BW ratio and oxidative stress in all groups, with the underlying pathological conditions of hypertension and hyperlipidemia having a weak yet direct effect on this relationship. Systemic oxidative stress, measured by animals 29,30 . Another proposed cause relates to the abundant synthesis and secretion of angiotensinogen by adipose tissue 31,32 , especially visceral tissue 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…There was also a signi cantly positive relationship between VisF / BW ratio and oxidative stress in all groups, with the underlying pathological conditions of hypertension and hyperlipidemia having a weak yet direct effect on this relationship. Systemic oxidative stress, measured by animals 29,30 . Another proposed cause relates to the abundant synthesis and secretion of angiotensinogen by adipose tissue 31,32 , especially visceral tissue 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the P-selectin (Selp) gene, reported to be upregulated in HFD-induced obese mice, increased with generations, suggesting local platelet activation and formation of monocyte-platelet conjugates. These cell-cell interactions could then contribute to local infl ammatory processes ( 25 ). The tendency toward additional proinfl ammatory pathways was also suggested by enhanced expression over generations of neurotensin (Nts), which is known to participate in the activation of the NF-B signaling pathway.…”
Section: Gene Expression Analysis Of Stromal Vascular Cellsmentioning
confidence: 99%
“…This is also the case with adipose tissue inflammation. Recent studies have demonstrated that obese adipose tissue exhibits adipocyte hypertrophy, immune cell infiltration, angiogenesis, and extracellular matrix overproduction during the progression of chronic inflammation [4,5,15,16]. In other words, stromal cells change dramatically in number and cell type during the course of obesity.…”
mentioning
confidence: 99%